Dermatite associada à incontinência: estudo de coorte em pacientes críticos - Paula Caroline Gonçales (2016)
The Intensive Care Unit (ICU) is the place for the care of critically ill patients during hospitalization and these are exposed to several factors that can lead to damage to the skin. Among such damage, dermatitis associated with incontinence (DAI). The overall objective of the study is to analyze the problem of DAI in adult patients admitted to the ICU of a public hospital in Belo Horizonte - MG. Since the main objectives were to identify the literature the risk factors for DAI in adult patients, to characterize patients who developed DAI estimate the incidence, determine the DAI risk factors in ICU and propose a risk predictionmodel. This is a study carried out in three stages: an integrative review (RI), degree of concordance and study concurrent cohort. The risk factors identified in DAI RI were age, comorbidities, nutrition, oxygenation, perfusion, temperature, fecal and / or urinary incontinence, mechanical friction, use irritants, cognitive ability. This yields an overall incidence of 20.4% and an incidence density of 2.5 cases / 100 person-days. They found 19 risk factors significantly associated with DAI. In the final model of risk prediction met: male, trauma, hypnotic / sedative, lactulona, nutritional support, loose stools and burning. The results showed that the DAI is a common finding in patients admitted to adult ICUs and therefore deserves special attention in order to have better quality of nursing care provided to these patients.